Clinical outcomes of femoral shaft non-union: dual plating versus exchange nailing with augmentation plating - Wei Zhang (Journal of Orthopaedic Surgery and Research, 2018)
Abstract Background By comparing clinical outcomes between dual plating (DP) and exchange nailing with augmentation plating (EN/AP), we aimed to provide better treatment strategies for femoral shaft non-union. Methods We retrospectively reviewed 30 patients with aseptic femoral shaft non-union at our level 1 trauma center between January 2014 and January 2017. All patients underwent a one-stage, definitive revision procedure, including DP for 16 patients and EN/AP for 14 patients. Perioperative surgical trauma, fracture healing, complications, and the time to return to work were evaluated. Results Twenty-nine patients achieved fracture healing. In the EN/AP group, the fracture healing rate was 100%, the healing time was 5.7 ± 1.7 months, and the time of return to work was 8.2 ± 2.9 months. In the DP group, the fracture healing rate was 94%, the healing time was 8.4 ± 4.1 months, and the time of return to work was 18.4 ± 10.3 months. In terms of fracture healing and return to work, the patients in the EN/AP group required less time than those in the DP group, and the differences were statistically significant (p = 0.024 and p < 0.01 respectively). Except for the length of the incision, the two groups showed no statistically significant differences in operative time, postoperative deformity, and complications. Conclusions Both EN/AP and DP are important surgical options for femoral shaft non-union. Compared to DP, EN/AP resulted in a shorter incision, faster fracture healing, and a shorter time to return to work. Trial registration ChiCTR-ORC-17014062